THE EFFECT OF DIFFERENT DOSES OF Bacillus sp. PROBIOTICS ON THE SURVIVAL RATE OF WHITE SNAPPER (Lates calcarifer) LARVAE - Dewita Sari, Ida Ayu Sawitri; Swasta, Ida Bagus Jelantik; Amelia, Jasmine Masyitha (Jurusan Perikanan dan Kelautan, 2025)
This study aims to analyze the effect doses of Bacillus sp. Probiotics on the survival rate of white snapper (Lates calcarifer) larvae. The research was conducted at the Gondol Research Institute for Mariculture, Bali, over a 20-day period using a Completely Randomized Design (CRD) with three treatments and three replications: P0 (control, without probiotics), P1 (3 mg/L), and P2 (5 mg/L). Observed parameters included water quality (nitrate, nitrite, ammonia, phosphate, temperature, pH, salinity, DO), total bacterial count (TBC), survival rate (SR), larval length, and hatching rate (HR). The results showed that the administration of Bacillus sp. probiotics had a significant effect on the survival rate of white snapper larvae (p < 0.05). Based on ANOVA, there were significant differences in SR between treatments. The Bonferroni post hoc test revealed that treatment P2 (5 mg/L) was significantly different from both the control (P0) and P1 (3 mg/L), with P2 producing the highest average SR of 84%, compared to P1 at 70.3% and the control at 50.3%. Meanwhile, probiotic administration did not have a significant effect (p > 0.05) on water quality parameters or larval length. The highest larval length was also recorded in treatment P2, with an average of 1.5 cm on day 20. The use of probiotics contributed to the reduction of toxic compounds such as nitrate, nitrite, and ammonia, and helped stabilize the rearing water environment. Based on these results, it can be concluded that the administration of Bacillus sp. probiotics at a dose of 5 mg/L is the optimal dosage for improving the survival rate of white snapper larvae and maintaining the quality of the aquaculture environment.